2020
DOI: 10.1186/s12890-020-01320-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of toner-handling work on respiratory function, chest X-ray findings, and biomarkers of inflammation, allergy, and oxidative stress: a 10-year prospective Japanese cohort study

Abstract: Background Exposure to toner, a substance used in photocopiers and printers, has been associated with siderosilicosis and other adverse effects. However, these findings are limited, and there is insufficient evidence on the long-term effects of toner exposure. Using longitudinal analysis, this study aimed to examine the effects of work involving toner exposure on the respiratory system over time. Methods We conducted a prospective cohort study in a Japanese toner and copier manufacturing enterprise between 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Dust concentration measurements in toner handling workplaces were evaluated through individual exposure measurements and workplace dust concentration measurements. As mentioned in the Terunuma paper [12,22], there were differences in individual exposure concentrations among work categories by toner operation, with significantly higher concentrations in the machine recycling and toner manufacturing work categories than in the other work categories. This trend is similar to that observed in the Kitamura paper [13], where results of individual exposure measurements showed that the average dust concentration over the 10-year observation period ranged from 0.109 to 0.215 mg/m 3 for toner manufacturing, 0.038 to 0.575 mg/m 3 for toner research and development, and 0.044 to 0.323 mg/m 3 for engineering.…”
Section: Work Environment Evaluationmentioning
confidence: 79%
See 4 more Smart Citations
“…Dust concentration measurements in toner handling workplaces were evaluated through individual exposure measurements and workplace dust concentration measurements. As mentioned in the Terunuma paper [12,22], there were differences in individual exposure concentrations among work categories by toner operation, with significantly higher concentrations in the machine recycling and toner manufacturing work categories than in the other work categories. This trend is similar to that observed in the Kitamura paper [13], where results of individual exposure measurements showed that the average dust concentration over the 10-year observation period ranged from 0.109 to 0.215 mg/m 3 for toner manufacturing, 0.038 to 0.575 mg/m 3 for toner research and development, and 0.044 to 0.323 mg/m 3 for engineering.…”
Section: Work Environment Evaluationmentioning
confidence: 79%
“…Changes in respiratory function over time due to toner exposure were estimated by stepwise multiple regression analysis. In the Terunuma paper [12,22], chi-square and Fisher's exact tests, simple t-test and Welch's t-test for quantitative variables, logistic regression analysis with generalized estimating equations (GEE), two-way repeated measures analysis of variance (ANOVA), and linear mixed models (LMM) were used. In all analyses, the significance level was less than 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations